KONFLIK BATIN TOKOH ZAHRANA DALAM NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN ELSHIRAZY - Diyan Permata Yanda, M.Pd (Jurnal Gramatika, 2015)
This article aims to reveal the structure of the novel and the inner conflict experienced Zahrana figures. Zahrana is a girl educated, intelligent, and achieving a dilemma when faced with the choice of pursuing goals, career, and marriage. Zahrana experienced inner conflict arises when there is a difference in her desire that want to continue education with the wishes of parents who want to get married. Her parents worried about her son would be called an old maid because never married. This concern stems from the view of society that a woman's primary duty is to be a mother to her children. Readers can reap the lessons of this novel with the existence of a series of character and his life journey.